Mathematical Values In Turkish High School Mathematics Textbooks - Damla BAKIRCI; Abdullah Çağrı Biber (Lectito Publications, 2022)
This study aims to examine how mathematical values are represented in Turkish high school mathematics textbooks during the 2019-2020 academic year. A case study design was used in this study. The research examined a total of 2175 questions. Descriptive analysis was used in the analysis of qualitative data. The data was sorted into mathematical value pairs. Three complementary pairing of mathematical values are considered: rationality-objectivism, control-progress, and openness-mystery. As a result of the analysis, it has been determined that the rationality-objectivism value pair is similar across all grade mathematics textbooks. The control value was also emphasized more than the progress value The openness value was highlighted more than complementary pairs of mystery values at the 9th, 10th, and 11th-grade levels. In comparison, the mystery value is emphasized more than the openness value in the 12th-grade textbook. As a result, it would be advisable to pay attention to the balanced distribution of complementary value pairs when considering the importance of mathematics values for mathematics textbooks.
Keywords: Eğitim Üzerine Çalışmalar; Objectivism; Turkish; Studies on Education; Social Sciences; Epistemology; Rationality; Social psychology; Educational Objectives; Education; Value (mathematics); Metaphors in Educational Research and Practice; FOS: Mathematics; Psychology; Trends in 21st Century Education Research; Openness to experience; Mathematical values; mathematics textbooks; high school; Turkey; Statistics; Linguistics; Mathematics education; FOS: Philosophy, ethics and religion; FOS: Psychology; Philosophy; Curriculum Alignment and Educational Objectives; FOS: Languages and literature; Arts and Humanities; Mathematics; 4. Education